2016
DOI: 10.1177/0885066615597198
|View full text |Cite
|
Sign up to set email alerts
|

Postintubation Hypotension in General Anesthesia

Abstract: Development of PIH occurs in 60% of patients undergoing intubation for vascular surgery and was associated with adverse outcomes including extended ICU LOS and postop ventilation requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Intra‐operative hypotension has been associated with postoperative acute kidney injury and death in other cohorts . Our results extend previous work by showing that depth and duration of hypotension, both before and after incision, were significantly associated with acute kidney injury, which is consistent with limited data from vascular surgery and emergency airway management .…”
Section: Discussionsupporting
confidence: 90%
“…Intra‐operative hypotension has been associated with postoperative acute kidney injury and death in other cohorts . Our results extend previous work by showing that depth and duration of hypotension, both before and after incision, were significantly associated with acute kidney injury, which is consistent with limited data from vascular surgery and emergency airway management .…”
Section: Discussionsupporting
confidence: 90%
“…We found that diuretic use increases risk of PIH. Sedation and the physiologic effects of positive pressure ventilation commonly results in blood pressure reduction surrounding ETI [9]. Therefore, hypovolemia due to diuresis would plausibly exacerbate blood pressure decreases.…”
Section: Clinical Utility Of Hyps and (S) Hypsmentioning
confidence: 99%
“…decreased systemic vascular resistance). However, this risk is not universally recognized and there is substantial variance in best practices associated with safer ETI processes in the ICU [6,9,[10][11][12][13][14][15][16][17]. Further, despite the above cited associations, there is no currently available formal method that predicts the onset of hypotension when an airway is established in the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…For example, peri-intubation hypotension has been associated with both increased length of stay and mortality [1][2][3]. Furthermore, this association has been identified not only in the critically ill but also in elective surgical patients [4,5]. Several studies indicate that the frequency with which peri-intubation hypotension occurs is fairly high, with one report indicating an incidence of greater than 80% [1,2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this association has been identified not only in the critically ill but also in elective surgical patients [4,5]. Several studies indicate that the frequency with which peri-intubation hypotension occurs is fairly high, with one report indicating an incidence of greater than 80% [1,2,5,6]. However, the data presented on the frequency is dependent on definitions currently used in the literature for which no standard consensus exists.…”
Section: Introductionmentioning
confidence: 99%